2009
DOI: 10.1016/j.bbrc.2008.10.155
|View full text |Cite
|
Sign up to set email alerts
|

TNFα is required for cholestasis-induced liver fibrosis in the mouse

Abstract: TNFα, a mediator of hepatotoxicity in several animal models, is elevated in acute and chronic liver diseases. Therefore, we investigated whether hepatic injury and fibrosis due to bile duct ligation (BDL) would be reduced in TNFα knockout mice (TNFα−/−). Survival after BDL was 60% in wild-type mice (TNFα+/+) and 90% in TNFα−/− mice. Body weight loss and liver to body weight ratios were reduced in TNFα−/− mice compared to TNFα+/+ mice. Following BDL, serum alanine transaminases (ALT) levels were elevated in TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 48 publications
6
71
0
Order By: Relevance
“…It offers protection to cells from oxidative damages induced by hydrogen peroxides and hydroperoxides (Gabele et al, 2009). In TCDD-intoxicated rats, there was an elevation in GSH level (p50.05) (Figure 3) in liver homogenates compared with vehicle control rats.…”
Section: Effect Of Oo Ht and Ty On Gsh Level During Tcdd Treatmentmentioning
confidence: 99%
“…It offers protection to cells from oxidative damages induced by hydrogen peroxides and hydroperoxides (Gabele et al, 2009). In TCDD-intoxicated rats, there was an elevation in GSH level (p50.05) (Figure 3) in liver homogenates compared with vehicle control rats.…”
Section: Effect Of Oo Ht and Ty On Gsh Level During Tcdd Treatmentmentioning
confidence: 99%
“…BC703 may reduce oxidative stress by recovery of antioxidative enzymes, together with decrease in lipid peroxidation and oxidative stress. However, TNF-α in BDL-induced cholestasis mediates acute and chronic liver injury and plays an important role in hepatic fibrosis and cirrhosis (Gäbele et al, 2009). Khanal et al (2009) reported that saponins isolated from the root of P. grandiflorum decreased the TNF-α level on acute ethanol-induced hepatic injury in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we first assessed PI3K p110γ mRNA expression in different murine models of chronic liver injury by quantitative PCR. We observed a significantly increased expression in the BDL model, which is a well established liver fibrosis model (Ezure et al, 2000,Gabele et al, 2009,Isayama et al, 2006 ( Fig. 4a), as well as in two dietary NASH models, namely the MCD model (Weltman et al, 1996) (Fig 4b) and a high fat diet (HFD) model (Fig 4c), which are also well established (Gabele et al, 2011b,Gabele et al, 2011a,Matsuzawa et al, 2007,Paigen et al, 1985.…”
Section: Iii1 Analysis Of Pi3k P110γ γ γ γ Expression In Diseased Mmentioning
confidence: 87%
“…The bile duct ligation model has already widely been used to evaluate genetic factors, which are associated with hepatic fibrogenesis. Experimental liver fibrogenesis is for example increased in IL-6 knockout mice, but decreased in TNF-and CD14 knockout mice (Ezure et al, 2000,Gabele et al, 2009,Isayama et al, 2006.…”
Section: I4 Experimental Models For Chronic Liver Disease I41 Thmentioning
confidence: 99%